Analisis Rasio Keuangan dalam Menilai Kinerja Keuangan Toko Pesona Bari Songket Palembang - Ghina Nur Wasilah Defa; M. Syahirman Yusi; Elisa Elisa (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2022)
This research discussed about the financial ratio at Pesona Bari Songket Palembang store with the aim to find out how the financial performance in Pesona Bari songket Palembang store using liquidity ratio and profitability ratio.The data types in this study used primary and secondary data. Primary data in the form of interviews conducted with the owner of Pesona Bari Songket store and secondary data in the form of financial statements of Pesona Bari Songket stores from 2016 to 2020.The results of the study can be concluded that the calculation of liquidity ratio in Pesona Bari Songket Palembang stores increased every year but still below the industry average standard in 2016 to 2019 while the profitability ratio is said to be less good on net profit margin, return on assets, return on equity and said to be good on gross profit margin.